Occupational Health And Safety Knowledge Level and Affecting Factors in Medical Faculty Students - Osmanoğlu, Vecdi; Uğraş Dikmen, Asiye (Turkey Health Literacy Journal, 2022)
Occupational physicians have an important role to play in the prevention of occupational diseases and work accidents. In our country,occupational medicine can be practiced by the ones who have graduated from medical school, received the title of medical doctor, have completed the occupational medicine course, passed the exam, and are authorized by the Ministry. In this case, it has great importancethat medical school students receive studies on work accidents and occupational diseases that they will encounter in their working life. The universe of this research was composed of students studying at Gazi University Faculty of Medicine, the class (term) of education was determined as stratum, and a questionnaire was applied to 396 students with the stratified sampling method. During their education,these students attend a public health committee in the 3rd grade, occupational health and workplace medicine in the 5th grade (elective),and public health internship in the 6th grade regarding occupational health and safety. There are 42 questions in the questionnaire and 24 of them are the questions measuring the level of knowledge about occupational health and safety. The highest score obtained is 20 and the lowest score is 0. The students who participated in the survey mostly answered, “I don’t know” to the questions measuring their level of knowledge. A statistically significant difference found between the classes of the students and in terms of their previous education status and in terms of occupational health and safety knowledge level. (p